Poetry's Afterlife Verse in the Digital Age - Stein, Kevin (University of Michigan Press, 2010)
"The great pleasure of this book is the writing itself. Not only is it free of academic and 'lit-crit' jargon, it is lively prose, often deliciously witty or humorous, and utterly contemporary. Poetry's Afterlife has terrific classroom potential, from elementary school teachers seeking to inspire creativity in their students, to graduate students in MFA programs, to working poets who struggle with the aesthetic dilemmas Stein elucidates, and to teachers of poetry on any level." --- Beckian Fritz Goldberg, Arizona State University "Kevin Stein is the most astute poet-critic of his generation, and this is a crucial book, confronting the most vexing issues which poetry faces in a new century." ---David Wojahn, Virginia Commonwealth University At a time when most commentators fixate on American poetry's supposed "death," Kevin Stein's Poetry's Afterlife instead proposes the vitality of its aesthetic hereafter. The essays of Poetry's Afterlife blend memoir, scholarship, and personal essay to survey the current poetry scene, trace how we arrived here, and suggest where poetry is headed in our increasingly digital culture. The result is a book both fetchingly insightful and accessible. Poetry's spirited afterlife has come despite, or perhaps because of, two decades of commentary diagnosing American poetry as moribund if not already deceased. With his 2003 appointment as Illinois Poet Laureate and his forays into public libraries and schools, Stein has discovered that poetry has not given up its literary ghost. For a fated art supposedly pushing up aesthetic daisies, poetry these days is up and about in the streets, schools, and universities, and online in new and compelling digital forms. It flourishes among the people in a lively if curious underground existence largely overlooked by national media. It's this second life, or better, Poetry's Afterlife, that his book examines and celebrates. Kevin Stein is Caterpillar Professor of English and Director of the Creative Writing Program at Bradley University and has served as Illinois Poet Laureate since 2003, having assumed the position formerly held by Gwendolyn Brooks and Carl Sandburg. He is the author of numerous books of poetry and criticism. digitalculturebooksis an imprint of the University of Michigan Press and the Scholarly Publishing Office of the University of Michigan Library dedicated to publishing innovative and accessible work exploring new media and their impact on society, culture, and scholarly communication. Visit the website at www.digitalculture.org.